Майже періодичні розв’язки нелінійних рівнянь, що можуть не бути майже періодичними за Бохнером - Слюсарчук, В.Ю. (Український математичний журнал, 2015)
Введен новый класс почти периодических операторов. Также получены условия существования почти периодических решений нелинейных уравнений, которые могут не быть почти периодическими по Бохнеру. We introduce a new class of almost periodic operators. We also establish conditions for the existence of almost periodic
solutions of nonlinear equations which are not necessarily almost periodic in Bochner’s sense.